Externalities and market failures of cryptocurrencies - Topi Hokkanen (Bank of Finland, 2023)
This paper discusses the externalities and market failures in cryptocurrency markets. In particular, I highlight the significant environmental externalities created by Proof-of-Work (PoW) cryptocurrencies, the most prominent of which is Bitcoin. The main goals of this paper are to quantify these externalities, illustrate the mechanisms by which they arise, and finally discuss feasible mechanisms to regulate them. Latest estimates show that Bitcoin mining consumes roughly the same amount of electricity as Argentina or Sweden, with commensurate carbon dioxide emissions. The two main factors driving these externalities are Bitcoin's electricity-intensive consensus protocol and Bitcoin prices, which directly influence mining incentives. Efficient supply-side regulation of these externalities is hamstrung by the internationally mobile nature of Bitcoin miners, creating a risk of carbon leakage and regulatory arbitrage in the absence of a global carbon tax. Moreover, the cryptocurrency market and exchanges themselves are to a high degree unregulated and opaque. This exacerbates the situation since cryptocurrency prices are directly linked to mining incentives. Instead of regulating the miners i.e. the supply side of the market, as the literature has broadly suggested, I recommend focusing on regulating the demand side, the exchanges and marketplaces, as a reasonable first step in the comprehensive regulation of cryptocurrencies. Cross-border coordination is likely to be a crucial aspect in mitigating the environmental externalities of cryptocurrencies.
URN:NBN:fi-fe20231026141509
Keywords: D62; E42; H23; Q54; Q58; 330; forecasting; investment; Tobin's Q; discrete wavelets; bitcoin; cryptocurrency; externalities; crypto mining